Wear resistance of the surface layers of hard alloys with a multilevel structural phase state; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 10, iss. 4 - Ovcharenko V. E. Vladimir Efimovich; Ivanov Yu. F. Yuriy Fedorovich; Mokhovikov A. A. Aleksey Aleksandrovich; Ivanov K. V. Konstantin Veniaminovich; Solonenko O. P. Oleg Pavlovich; Uljyanitsky V. Yu. Vladimir Yurjevich; Beliy A. V. Aleksey Vladimirovich; Bao Hai Yu; Zhang H. Honwei (2016, 2016)
Title screen